Comparative study of the effect of gamma-radiation on the structural and thermophysical properties of nitrile-butadiene rubber filled with different nanometal oxides - Khankishiyeva, R.F.; Mammadov, S.M.; Akhundzada, H.N.; Mammadov, J.S.; Azadaliyev, A.I.; Ismayilova, P.I.; Mammadova, G.A. (Вопросы атомной науки и техники, 2020)
In the present work, the structure and thermal properties of nanocomposites based on nanometal oxides (ZnO, Al₂O₃, ZrO₂) and aromatic disulphochloride benzene compounds in a butadiene nitrile rubber (NBR) matrix that are obtained by gamma-rays processing have been investigated. Structural changes of nanocomposites depend on the type of used nanoparticles which have been identified by Fourier Transform Infrared (FTIR) spectroscopy and Electron Paramagnetic Resonance (EPR). Analysis by Scanning Electron Microscope (SEM) was used to study the morphology phase of the nanoparticles in the polymer matrix and the interface between the polymer-filler. In addition, the results of the samples based on NBR were obtained by thermogravimetric analysis (TGA)/differential thermal analysis (DTA). The results show that, the thermal stability of nanocomposites significantly decreased after irradiation, but with the addition of a certain amount of benzene-1,3-disulfonyl chloride (DSChB) and nanometal oxides to rubber blend the thermal stability could be improved. Досліджено структуру і термічні властивості нанокомпозитів на основі різних нанооксидів металів (ZnO, Al₂O₃, ZrO₂) і ароматичних дісульфохлорідних бензольних сполук у матриці бутадієн-нітрильного каучуку (БНК), отриманого при обробці гамма-випромінюванням. Cтруктурні зміни нанокомпозитів у залежності від типу використаних наночастинок були досліджені за допомогою методів ІЧ-фур'є- і ЕПР-спектроскопії. Для вивчення морфології наночастинок у полімерній матриці і границі розділу фаз у системі полімер–наповнювач використовували скануючий електронний мікроскоп (СЕМ). Крім того, за допомогою термогравіметричного (ТГА)/диференціального термічного аналізів (ДTА) були вивчені термічні властивості зразків на основі БНК. Результати показують, що термостабільність нанокомпозитів значно знижується після опромінення, але при додаванні певної кількості бензол-1,3-дисульфонілхлориду (ДСХБ) і нанорозмірних оксидів металів термостійкість суміші каучуку може бути поліпшена. Исследованы структура и термические свойства нанокомпозитов на основе различных нанооксидов металлов (ZnO, Al₂O₃, ZrO₂) и ароматических дисульфохлоридных бензольных соединений в матрице бутадиен-нитрильного каучука (БНК), полученного при обработке гамма-излучением. Cтруктурные изменения нанокомпозитов в зависимости от типа использованных наночастиц были исследованы с помощью методов ИК-фурье- и ЭПР-спектроскопии. Для изучения морфологии наночастиц в полимерной матрице и границы раздела фаз в системе полимер–наполнитель использовали сканирующий электронный микроскоп (СЭМ). Кроме того, с помощью термогравиметрического (ТГА)/дифференциального термического анализов (ДTА) были изучены термические свойства образцов на основе БНК. Результаты показывают, что термостабильность нанокомпозитов значительно снижается после облучения, но при добавлении определенного количества бензол-1,3-дисульфонилхлорида (ДСХБ) и наноразмерных оксидов металлов термостойкость смеси каучука может быть улучшена.